2015
DOI: 10.1016/j.carbpol.2014.12.059
|View full text |Cite
|
Sign up to set email alerts
|

Thixotropic properties of normal potato starch depending on the degree of the granules pasting

Abstract: The aim of this paper was the study of the rheological instability (thixotropy and/or antithixotropy) of normal potato starch (NPS) pastes depending on their concentration (2-5%) and degree of pasting. Flow curves with hysteresis loops, apparent viscosity at constant shear rate and in-shear structural recovery tests were carried out. Granule size profiles, the pasting characteristic of corresponding starch suspensions and the transmittance of the pastes, the molecular weights and polydispersity of granular sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
50
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 70 publications
(58 citation statements)
references
References 42 publications
6
50
2
Order By: Relevance
“…Thixotropic behaviour of native cereal starch gels confirmed inhomogenity of these mixtures: they contained not only pasted granules but also swollen and partially pasted granules. As it was confirmed by Krystyjan et al (2016) and Sikora et al (2015), the pasting temperature of starch significantly influenced the rheological parameters of the resulted gels which may have thixotropic, antithixotropic or mixed thixotropic/ T a b l e 3. antithixotropic characteristics. The authors confirmed that at 95°C incomplete starch pasting took place.…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…Thixotropic behaviour of native cereal starch gels confirmed inhomogenity of these mixtures: they contained not only pasted granules but also swollen and partially pasted granules. As it was confirmed by Krystyjan et al (2016) and Sikora et al (2015), the pasting temperature of starch significantly influenced the rheological parameters of the resulted gels which may have thixotropic, antithixotropic or mixed thixotropic/ T a b l e 3. antithixotropic characteristics. The authors confirmed that at 95°C incomplete starch pasting took place.…”
Section: Resultsmentioning
confidence: 81%
“…The areas of thixo-and antithixotropy hysteresis loops were calculated according to Sikora et al (2015) by the summing-up of the areas of particular trapeziums formed between the curve 'up' and 'down'.…”
Section: Methodsmentioning
confidence: 99%
“…The areas of the hysteresis loop were calculated by summation of the areas of trapeziums situated between ascending and descending curves. The power of thixotropy in the volume of the sample was calculated as a function of the shear rate (Sikora et al, 2015). Rheological properties were analysed by fitting the Ostwald -de Waele rheological model (1) to the flow curves taken at shear rate increasing from 0 to 300 s -1 :…”
Section: Methodsmentioning
confidence: 99%
“…In-shear structural recovery test with pre-shearing was carried out according to the procedures of Mezger (2002), Achayuthakan and Suphantharika (2008), Wang et al (2009;2010), modified by Sikora et al (2015), as follows: 1) preshearing -a constant shear rate of 100 s -1 for 30 s, 2) relaxation -a zero shear rate for 300 s, 3) a constant shear rate of 1 s -1 for 120 s, 4) a constant shear rate of 300 s -1 for 60 s, 5) a constant shear rate of 1 s -1 for 240 s. The results enabled calculations of the degree of structure recovery (DSR) of the pastes according to Wang et al (2009;2010) -the ratio of the average apparent viscosity in the fifth (obtained in the first 120 s) and the third step were considered.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation